Digital Mentorship: Mentor-Mentee Relationships in Virtual Spaces - Seyed Ali Tabar, Seyed Hadi; Zadhasn , Zohreh (AI and Tech in Behavioral and Social Sciences, 2023)
This study aims to explore the experiences, challenges, and outcomes of digital mentorship, categorizing the different facets of mentor-mentee interactions in virtual environments and identifying effective strategies for digital mentorship. Employing a qualitative research design, this study conducted semi-structured interviews with 25 participants who have been involved in digital mentorship either as mentors or mentees. Thematic analysis was used to identify key themes and categories from the interview transcripts, focusing on communication methods, challenges and solutions, professional development, personal development, and the role of technology and tools in facilitating mentorship. The analysis revealed five main themes: Communication Methods, Challenges and Solutions, Professional Development, Personal Development, and Technology and Tools. Each theme encompasses various categories and concepts, such as synchronous and asynchronous communication, technical issues and cultural differences, skill acquisition and networking, confidence building and work-life balance, and the utilization of collaboration platforms and communication tools. These findings highlight the diversity of practices and experiences in digital mentorship, along with the strategies employed by participants to navigate the challenges of virtual environments. Digital mentorship presents a complex, multifaceted landscape that offers both challenges and opportunities for mentor-mentee relationships. Effective communication, strategic use of digital tools, and attention to personal connection are crucial for maximizing the benefits of mentorship in virtual spaces. This study contributes to the understanding of digital mentorship dynamics, providing insights for enhancing mentorship practices and outcomes in the digital age.